2008
DOI: 10.1007/s10751-008-9875-6
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic studies of Bi x Y3-x Fe5O12 fabricated using conventional method

Abstract: The effect of Bi 3+ substitution for Y 3+ on lattice constants, morphology and magnetic properties of pure YIG has been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…This results in the decrease of M s . Furthermore, the effect of Bi 3 þ atomic weight on the density of Bi-substituted YIG is more dominant than its effect of the ionic radius [29,30]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…This results in the decrease of M s . Furthermore, the effect of Bi 3 þ atomic weight on the density of Bi-substituted YIG is more dominant than its effect of the ionic radius [29,30]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Its ferrimagnetism results from superexchange interactions [55] between octahedral and tetrahedral Fe 3+ cations, which are antiparallel. As a bulk, YIG is commonly prepared by the classic solid-state reaction technique which involves temperatures as high as 1350°C, for a few hours [47]. Nanostructured YIG (or other garnet) is typically prepared by combining soft chemistry, or ball milling, and annealing to complete the reaction before SPS sintering.…”
Section: Soft Magnets: Garnetsmentioning
confidence: 99%
“…While, the observed decrease in saturation magnetization are attributed to either splitting of a and d sites to inter-sublattices with different canted magnetic moment directions [13] or the effect of atomic weight on its density [14,15]. Several authors suggested that, the increase in magnetization is attributed to an increase in superexchange interaction [19]; iii) charge-transfer of an electron from an oxygen p orbital to an antibonding e orbital of 3 Fe  at d site [20] and iv) mixing of the 6p orbitals of the bismuth with the oxygen 2p and iron 3d orbitals [21,22].…”
Section: Introductionmentioning
confidence: 98%